Culling structured hosts to eradicate vector-borne diseases - Xinli Hu; Yansheng Liu; Jianhong Wu (Mathematical Biosciences and Engineering)
A compartmental model is developed, in the form of a nonautonomoussystem of delay differential equations subject to impulses atspecific times, for mosquito-born disease control involvinglarvicides and insecticide sprays. Sufficient conditions in terms ofthe frequencies and rates of larvicides and insecticide sprays arederived, and numerical simulations are provided to illustrate thesharpness of these disease eradication conditions.